2014
DOI: 10.1245/s10434-014-4088-5
|View full text |Cite
|
Sign up to set email alerts
|

Modified Pringle Maneuver for Laparoscopic Liver Resection

Abstract: Background. The Pringle maneuver is widely used in liver surgery to reduce intraoperative blood loss.1 However, total vascular inflow occlusion is frequently associated with ischemia reperfusion injury leading to postoperative liver dysfunction and impaired recovery. 2-4We describe herein an original procedure of modified Pringle maneuver (MPM) during laparoscopic liver resection with selective clamping of hepatic arterial inflow. Methods. Of 183 laparoscopic major hepatectomies performed at the Institute Mutu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…This procedure results in splenic congestion and consequently, poor blood perfusion in the liver, stomach, small intestine, anterior part of the large intestine, pancreas, and spleen [4–8]. Upon restoring blood flow to the ischemic region, the injuries caused by ischemia might be aggravated further [9–12]. …”
Section: Introductionmentioning
confidence: 99%
“…This procedure results in splenic congestion and consequently, poor blood perfusion in the liver, stomach, small intestine, anterior part of the large intestine, pancreas, and spleen [4–8]. Upon restoring blood flow to the ischemic region, the injuries caused by ischemia might be aggravated further [9–12]. …”
Section: Introductionmentioning
confidence: 99%
“…3,7 On the other hand, portal triad clamping is an effective method to control intraoperative bleeding and can be adopted even in laparoscopic hepatectomies. 2,13 Many reports have shown that the reduction of cardiac preload results in a significant reduction of blood loss, thus decreasing hepatic veins congestion. 14,15 Historically, central venous pressure (CVP) has always been used to measure preload in open surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][18][19][20][21][22][23][24][25][26] Liver resectability was always confirmed by intraoperative ultrasonography. Major hepatectomy was defined as the resection of 3 or more contiguous segments.…”
Section: Surgical Proceduresmentioning
confidence: 92%